Body image dissatisfaction in adolescent girls in puberty (Research, Society and Development, 2021)
The aim of this study was to analyze body image satisfaction among girls from different pubertal groups using two assessment instruments. The sample consisted of 82 adolescent girls, aged 11 to 14 years, divided into two groups: pre- and post-menarche. The Kakeshita’s Body Image Scale (BIS) and Body Shape Questionnaire (BSQ) were used to assess body image dissatisfaction. For comparisons of anthropometric variables between pubertal groups, Student's t-test was used for independent samples. Comparisons between BMI classifications, body image satisfaction and desire for body image change were performed using chi-square and binomial tests for both groups. For the comparison between the instruments, the Kappa coefficient (K) was calculated. The results showed that, for BIS, more than 81% of adolescents showed dissatisfaction, being higher among adolescents in post-menarche. For BSQ, the prevalence of body dissatisfaction was lower, but the results did not confirm those previously observed. In both instruments (BIS and BSQ), there were no differences between groups. However, the study indicated a tendency for post-menarche girls to show greater dissatisfaction in relation to pre-menarche adolescents, while the instruments used do not show agreement in the results.